Review of the genus Eugryllacris Karny, 1937 (Orthoptera: Gryllacridinae) from China - Bian, Xun; Shi, Fuming (Zootaxa, 2016)
The Chinese species of Eugryllacris are reviewed. One new combination and six new species from China are described: Eugryllacris cylindrigera (Karny, 1926) com. nov., Eugryllacris bifoliata Bian & Shi sp. nov., Eugryllacris elongata Bian & Shi sp. nov., Eugryllacris fanjingshanensis Bian & Shi sp. nov., Eugryllacris lobulis Bian & Shi sp. nov., Eugryllacris longifissa Bian & Shi sp. nov. and Eugryllacris xiei Bian & Shi sp. nov.. A key to the species of Eugryllacris from China and a distribution map are presented. This paper is based on the material from the collection of the Museum of Hebei University.